2016
DOI: 10.1189/jlb.3ma0616-287r
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes and dendritic cells are the primary sources of interleukin 37 in human immune cells

Abstract: The interleukin (IL)-1 family member IL-37 is one of few anti-inflammatory cytokines, and it is capable of countering a broad spectrum of proinflammatory assaults. Although it is known that leukocytes are a major source of IL-37, knowledge on IL-37 production and secretion in specific immune cell types remains limited. Thus, we investigated IL-37 mRNA expression as well as protein production and secretion in human PBMCs. In PBMCs stimulated with agonists of Toll-like receptors (TLRs) 1-6 and 9, (the IL-37-enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 62 publications
6
49
0
Order By: Relevance
“…The difference in results between our results and the previous experiments published by Ballak et al [15] may be due to differences in methods to monitor food intake. In addition, non-littermates were used in the first experiment in this paper and in the study by Ballak et al [12]. Therefore, the reduction in fat mass and metabolic phenotype that were found initially could also be due to differences in genetic make-up or composition of gut microbiota [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in results between our results and the previous experiments published by Ballak et al [15] may be due to differences in methods to monitor food intake. In addition, non-littermates were used in the first experiment in this paper and in the study by Ballak et al [12]. Therefore, the reduction in fat mass and metabolic phenotype that were found initially could also be due to differences in genetic make-up or composition of gut microbiota [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The first studies into the function of IL-37 showed that it is a natural suppressor of innate inflammatory and immune responses [10]. In humans, several tissues and cell types express IL-37, including blood monocytes [11,12], epithelial cells [13], endothelial cells [14] and, importantly, also adipocytes [9,15]. IL-37 mRNA is degraded in the absence of inflammation, but upon lipopolysaccharide (LPS) stimulation, that is, a pro-inflammatory stimulus, IL-37 expression increases [16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The primers used for amplifying the IL-10 were: forward 5′-GCC TAA CAT GCT TCG AGA TC-3′; reverse 5′-TGA TGT CTG GGT CTT GGT TC–3′ [21]; IL-37: forward 5′-TCA GCT GAA GAA GGA GAA ACT G-3′; reverse 5′-TTA TCT GTC ACC CCA ACA GG-3′ [22]. …”
Section: Methodsmentioning
confidence: 99%
“…IL-37 has not been widely studied, perhaps because its mouse homologue is still unidentified [18]. Its expression is relatively low in human cells under physiological conditions, but monocytes are the main producers of IL-37 within human peripheral blood mononuclear cells (PBMCs) [19]. Both IL-37 precursor (pro-IL-37) and processed forms (mIL-37) are biologically active, although the mIL-37 monomer has higher anti-inflammatory potency [20].…”
Section: Introductionmentioning
confidence: 99%